PROGRAM PLANNING AND PRACTICES FOR EFFECTIVE EARLY CHILDHOOD CARE AND EDUCATION: A STUDY (International Journal of Food and Nutritional Sciences, 2022)
Programmes for early childhood education have been greatly impacted by the shifting social,political, economic, and demographic landscapes. It used to be thought that a person's early years, frompregnancy to age five, set the stage for the instillation of information and abilities in them